The Sociodemographic Features of Patients Hospitalized at a Center For Addiction - Bilici, Rabia; Uğurlu, Görkem Karakaş; Tufan, Evren; Güven, Tuğba; Uğurlu, Mustafa (Fırat University, 2012)
Objective: The prevalence of substance use and related disorders both in the world and in our country is increasing. Retrospective evaluation of alcohol and substance use disorders and co-morbid psychopathologies may increase our knowledge on clinical features and treatments of those disorders. Materials and Methods: It was aimed to determine the socio-demographic and clinical features, psychopathologies co-morbid with alcohol/ substance use disorders and evaluate suggested treatments of patients hospitalized at the Treatment Center for Alcohol and Substance Use Disorders (AMATEM) of a regional hospital. Charts of patients were reviewed retrospectively, socio-demographic and clinical data were entered into a database prepared with Statistical Package for Social Sciences for WindowsTM 16.0 and descriptive statistics were used in analysis. Results: 258 male patients were included in the study. The most common applications for treatment were from Elazig (n= 77, 29.8 %) and Van (n= 36, 14.0 %) counties. The substance most frequently used among patients was cannabis (n= 133, 51.6 %) and the patients applied for treatment mostly probationary treatment processes (n=131, 50.8 %). The most common axis I diagnosis was Anxiety Disorders (n=58, 22.5 %) while the most common diagnosis on axis II was Anti-social personality disorder (n=30, 11.6 %). Conclusion: The majority of the patients who applied to AMATEM used probationary treatment processes. Most of the patients had primary or secondary education and declared that their socio-economical status were in low-middle classes. The prevalence of cannabis use among applications may reflect the process of probationary treatment. It was thought that our results may help in comparative evaluation of applications to AMATEM of various regions of our country.

Amaç: Madde kullanımı ve ilişkili bozuklukların, dünyada ve ülkemizde yaygınlığı giderek artmaktadır. Alkol ve madde kullanım bozukluklarının ve eşlik eden psikopatolojilerin geriye dönük değerlendirilmesi bu bozuklukların klinik özellikleri ve tedavileri hakkında bilgilerimizi artırabilir. Gereç ve Yöntem: Bu çalışmada bir yıllık süre içerisinde bir bölge hastanesinin AMATEM kliniğinde yatırılarak tedavi edilen hastaların sosyodemografik ve klinik verilerinin belirlenmesi, alkol/ madde kullanım bozukluğuna eşlik eden psikopatolojilerin ve önerilen tedavilerin gözden geçirilmesi amaçlanmıştır. Hastaların yatış dosyaları geriye dönük olarak taranmış, sosyodemografik ve klinik verileri Stastical Package for Social Sciences for WindowsTM 16.0 ile hazırlanan bir veritabanına kaydedilmiş ve analizlerde tanımlayıcı istatistikler kullanılmıştır. Bulgular: Çalışmaya, tümü erkek olan 258 hasta dahil edilmiştir. Tedavi başvurularının en sık kaynak aldığı iller Elazığ (n: 77, % 29.8) ve Van'dır (n: 36, % 14.0). Hastalar arasında en sık kullanılan maddenin esrar olduğu (n=133, % 51.6) ve hastaların en sık denetimli serbestlik süreci ile tedavi başvurusunda bulundukları gözlenmiştir (n=131, % 50.8). En sık I. Eksen tanısının Anksiyete Bozuklukları (n=58, % 22.5); en sık II. Eksen tanısının ise Anti-sosyal Kişilik Bozukluğu (n=30, % 11.6) olduğu saptanmıştır. Sonuç: Denetimli serbestlik süreci içerisinde tedavi olmak amacıyla başvuran hastalar örneklemin önemli bir bölümünü oluşturmaktadır. Çoğu hasta ilk ve orta öğretim düzeyinde eğitim görmüştür ve alt-orta gelir düzeylerinde olduklarını bildirmiştir. Başvurular arasında esrar kullanımının yaygınlığı denetimli serbestlik sürecini yansıtabilir. Bulgularımızın ülkemizin çeşitli bölgelerindeki AMATEM'lerine yapılacak başvuruların karşılaştırmalı olarak değerlendirilmesi için bir katkı sağlayabileceği düşünülmüştür.
Bir Bağımlılık Merkezinde Yatarak Tedavi Gören Hastaların Sosyodemografik Özellikleri